Pengenalan dan Penerapan Teknologi Informasi kepada Siswa Sekolah Dasar 122337 untuk Meningkatkan Literasi Digital - Rizky Nurhasanah; Yuegilion Pranayama Purba; Rahma Dhea Safitri; Regita Audyna Siregar; Victor Asido Elyakim P (Yayasan Literasi Sains Indonesia, 2025)
This community service program aims to introduce and equip sixth-grade students at SD Negeri 122337 with fundamental digital literacy skills. Digital literacy is an essential competency in navigating the increasingly complex digital era, especially for younger generations. The program was conducted over two days by lecturers and students from STIKOM Tunas Bangsa Pematangsiantar, using participatory and engaging learning methods. The implementation strategies included interactive material delivery, hardware usage demonstrations, and hands-on practice with educational software. The results indicated a significant improvement in students' understanding of technology usage. Students not only gained functional knowledge about technology but were also trained to use it wisely and productively in both educational contexts and daily life. The evaluation was carried out qualitatively through observations and direct student feedback. This program demonstrates the effectiveness of educational approaches in enhancing digital literacy at the elementary school level. Although there were limitations in direct practical facilities, visualization and reflective discussion methods proved effective in building students' understanding and confidence. This program is an important first step in preparing the younger generation to face the challenges of the digital era.